Karawitan Composition Brama Rupa | Komposisi Karawitan Brama Rupa - kadek samego; Tri Haryanto (GHURNITA: Jurnal Seni Karawitan, 2021)
This musical composition was created to apply the meaning of fire in the implementation of the yadnya ceremony in Bali. Brama Rupa is an innovative musical composition that applies the meaning of fire in Yadnya ceremony activities in Bali. This compositional work uses the combined expression of Gamelan Selonding and several Semar Pegulingan Gamelan instruments as well as additional instruments. The cultivation process uses the Alma M. Hawkins method in his book “Creating Through Dance”. He stated that the creation of a work of art was taken through three stages, namely the exploration stage, the improvisation stage, and the forming stage. This work is carried out in three parts, each of which is connected with a transitional term in Balinese terms (penyalit), supported by 15 musicians including stylists, presented independently (video taken) with a duration of 12 minutes.